Gender in Volunteering: Civil Society in Marrakech-Safi, Morocco (American Journal of Social Development and Entrepreneurship, 2025)
The study of volunteering and gender in age of contemporary society. It examines the impact of gender stereotypes and cultural perceptions on volunteering practices and motivations, and it also examines the manner in which volunteering neither challenges nor promotes traditional gender roles. The paper aims to provide insights into the perceptions of male and female volunteers and their influence on gender dynamics in the Marrakech Safi Region through a multidisciplinary analysis (using case study and empirical analysis). The research aims to contribute to understanding the role and organization of volunteering in contemporary social structures of volunteering in contemporary social structure and in gender relations.